Analysis of cost minimization methods in geo-distributed data centers - Khalaf, Ayesheh Ahrari; Hassan Abdalla Hashim, Aisha (The Institute of Electrical and Electronics Engineers, Inc., 2016)
Significant growth of Big Data leads to a great opportunity for data analysis. Data centers are continuously becoming more popular. At the same time data centers’ cost are increasing as the amount of data is growing. Simply as Big Data is significantly increasing, data centers are facing new challenges. Hence the idea of geo-distributed data center is introduced. This paper investigates on the main challenges that data centers face and presents analyses for cost minimization methods. Parameters involved are analyzed. Simulation results show that joint parameters techniques outperformed separate parameter techniques. Keywords—cloud computing; cost minimization; geodistributed data centers.